Rural Land Rights, Markets, and Structural Transformation: A Review of a Ugandan Case - Noel Kishaija; Bálint Heil (Land)
Uganda is gradually transitioning from communal to private land tenure systems. However, establishing privatized land rights has faced ongoing criticism, particularly concerning their impact on vulnerable groups. Despite the enactment of a national land policy, its benefits have not fully reached rural populations. Issues of land tenure insecurity and unclear ownership continue to generate confusion and have reportedly weakened traditional communal land systems, undermining sustainable agricultural production and long-term investment. This paper examines rural land rights, land markets, and the broader structural transformation of Uganda’s land sector, drawing on the existing literature and published reports. This review reveals that land tenure and administrative challenges persist, largely due to the dominance of customary tenure systems. Although land markets are active, they remain imperfect due to tenure insecurity and legal ambiguities. The findings highlight the need for increased public sensitization regarding land policy, gender-sensitive policies that promote joint ownership, continuous incentives for formalization, the acquisition of land documents, and the harmonization and strengthening of relevant land governance institutions.